Tribotechnical automated evaluation system for lubricating processes in friction fume - Мікосянчик, О.О.; Запорожець, О.І.; Мнацаканов, Р.Г. (Problems of Tribology, 2016)
The paper presents the results of the research conducted on a device for evaluation of tribotechnical characteristics of the trybocomponets. The software of the device registers and processes in real-time and with graphical presentation of changes - the moment of friction, turnover speed, lubricant temperature, voltage drop in contact lubricant layer. The analysis of the tribotechnical characteristics in contact at the startup moment under conditions of straight rolling and under the gradual increase of contact load has defined the decrease in contact energy load in the kinetics of friction changes due to high carry-ing capacity of the lubricant boundary adsorption layers, which characterized by non-Newtonian properties and demonstrate high anti-friction ability.